Comparative Study of the Comprehensive Properties of Multiwalled Nanotubes/Polyurethane Nanofibrous Membranes with and without Thermal Treatment. (28th March 2012) - Liu, Ling; Pan, Shengqiang
Abstract : This paper makes use of electrospinning technology to produce multiwalled nanotubes and polyurethane (MWNTs/PU) composite nanofibrous membranes. A thermal treatment method was proposed to improve the comprehensive properties of the membranes. The morphology of the prepared nanomaterials was characterized by the SEM and TEM. Comprehensive properties, including thermal stability, conductivity, and mechanical properties, of the membranes with and without thermal treatment were investigated comparatively by TGA, DMA, resistivity measurement, and tensile testing, respectively. The results indicate that the proposed thermal treatment method could effectively improve the conductivity and mechanical properties of the nanomaterials. For the thermal treatment-based membrane filled with 3 wt.% of MWNTs, the conductivity reaches 8.29 × 10 − 5 Scm −1, which is nearly three orders higher than that of the untreated sample. Meanwhile, the tensile strength and modulus increase more than 50% after thermal treatment. It is expected that such improved nanomaterials may be potentially useful in composite reinforcement and electronic devices.